Workers' perceptions of earnings growth and employment risk - Gizem Koşar; Wilbert van der Klaauw (Federal Reserve Bank of New York, 2023)
In addition to realized earnings and employment shocks, forward-looking individuals are presumed to condition their consumption and labor supply decisions on their subjective beliefs about future labor market risks. This paper analyzes these perceptions of earnings and employment risks using rich monthly panel data. It documents considerable individual heterogeneity in expected earnings growth and earnings growth uncertainty and in the perceived likelihood of a voluntary and involuntary job exit. We examine how these expectations evolve over the working life and the business cycle, and how they co-vary with expectations about the macro economy. Our analysis provides novel evidence on the perceived persistence in earnings growth shocks and on the association between future earnings and spending growth.
Keywords: D84; D81; J31; J63; D12; C23; 330; expectations data; beliefs; household surveys; strategic survey questions; labor market uncertainty; wage persistence